Ephenidine: A new psychoactive agent with ketamine-like NMDA receptor antagonist properties. (January 2017) - Kang, Heather; Park, Pojeong; Bortolotto, Zuner A.; Brandt, Simon D.; Colestock, Tristan; Wallach, Jason; Collingridge, Graham L.; Lodge, David
Abstract: To avoid legislation based on chemical structure, research chemicals, frequently used for recreational purposes, are continually being synthesized. N -Ethyl-1, 2-diphenylethanamine (ephenidine) is a diarylethylamine that has recently become popular with recreational users searching for dissociative hallucinogenic effects. In the present study, the pharmacological basis of its neural actions has been investigated, initially by assessing its profile in central nervous system receptor binding assays and subsequently in targeted electrophysiological studies. Ephenidine was a potent inhibitor of 3 H-MK-801 binding (Ki: 66 nM), implying that it acts at the PCP site of the N -methyl-d -aspartate (NMDA) receptor. It also showed modest activity at dopamine (379 nM) and noradrenaline (841 nM) transporters and at sigma 1 (629 nM) and sigma 2 (722 nM) binding sites. In experiments of extracellular recording of field excitatory postsynaptic potentials (fEPSPs) from area CA1 of rat hippocampal slices, ephenidine, 1 and 10 μM, respectively, produced a 25% and a near maximal inhibition of the NMDA receptor mediated fEPSP after 4 h superfusion. By contrast, ephenidine (50 μM) did not affect the AMPA receptor mediated fEPSPs. In whole cell patch clamp recordings, from hippocampal pyramidal cells, ephenidine (10 μM) blocked NMDA receptor-mediated EPSCs in a highly voltage-dependent manner. Additionally, ephenidine, 10 μM, blocked the induction of long term potentiation (LTP) in CA1 induced by theta burst stimulation. The present data show that the new psychoactive substance, ephenidine, is a selective NMDA receptor antagonist with a voltage-dependent profile similar to ketamine. Such properties help explain the dissociative, cognitive and hallucinogenic effects in man. This article is part of the Special Issue entitled 'Ionotropic glutamate receptors'. Highlights: New 'legal high', the dissociative ephenidine, displaces MK-801 binding. Ephenidine, like ketamine, blocks NMDA receptor mediated synaptic potentials and plasticity. Ephenidine, like ketamine, blocks the NMDA receptor in a highly voltage-dependent manner. Ephenidine blocks long-term potentiation, LTP. NMDA receptor antagonism likely underlies the psychoactive effects of ephenidine.